Nghiên cứu điều tra các chất ức chế proteinase ở các phần khác nhau của thân và hạt cây tô mộc (Caesalpinia sappan L.) - Hoàng, Thu Hà (Đại học Quốc gia Hà Nội, 2016)
Caesalpina sappan wood is widely used in oriental medicine. In Vietnamese traditional medicine it has been used for treatment of rheumatism, inflammatory, infection and other disease. There have been many papers about chemical compositions of C. sappan wood but none of them related to (PIs). As is known, PIs play an important role in regulation of different living processes and they are good candidates for development of new drugs. C.sappan belongs to Caesalpiaceae plant family, and the seeds of this plant family is known as a PIs-rich source. However, so far, no publication related to PIs from C. sappan seeds has been found. The aim of this work is to determine the effect of wood and seeds extracts on the activity of trypsin, chymotrypsin, proteinases isolated from P. aeruginosa and to study the conditions to partly purify the proteinase inhibitors coming from C. sappan seeds. The results obtained have indicated that: C. sappan bark and heartwood extracts exhibit inhibitory activity against trypsin and chymotrypsin. The trypsin inhibitory activity (TIA) and chymotrypsin inhibitory activity (ChIA) in 50% aqueous extract from bark are found to be 52.45 IU and 74.94 1U/100g, respectively, while those from heartwood are only 6.11 IU and 22.44 IU/100g, respectively.. C. sappan dormant seeds extract possesses TIA, ChIA as well as inhibitors against P. aeruginosa proteolytic enzymes (PPsIA). The PPsIA of seed coats is around 170IU/100g, that is 5 times higher than that of coat-free seeds. The use of 1/15M, pH 6,5 Sorensen buffer allows us to extract, at a high level, both TI and ChI. The TIA and ChIA of coat-free seeds (c-f-s) reach a level around 302 IU and 1049 IU/100g. The electrophoretic patterns of TI and ChI from c-f-s extract are very similar: 7 inhibitor bands were detected on the gel. These bands are located in two zones: the first one (at least 3 bands) corresponds to proteins of Mr higher than 43 kD and the other one (with 3 bands) to proteins with Mr from 20 — 30 kD; another band is equivalent to 14 kD. The PPsI bands zone is corresponding to protein bands of Mr higher than 67kD. Fractionation of c-f-s extract on Sephadex G-75 or G-100 column, one active peak (D2) has been obtained. The inhibitory activity yield of D2 is more than 90% of extract and their specific activities increase from 3 to 4 times. Thus, it has been suggested that the column chromatography on Sephadex G-75 or G-100 gel can be used at the first step for purification of TI/ChI from C. sappan seeds.